Politik Identitas dan Perlawanan Kolektif terhadap Otoritas: Studi Kasus Polresta Deli Serdang - Syahputra, Romi; Nasution, Hasyimsyah; Azhar, Anang Anas (Medan Resource Center, 2025)
This study investigates how identity politics informs collective resistance to state authority, with a specific focus on the Polresta Deli Serdang in North Sumatra during a controversial drug raid. The objective is to understand how religious and ethnic symbols were mobilized to construct communal solidarity, trigger emotional escalation, and frame law enforcement as an external, even hostile, force. Using a qualitative case study method, the research explores how resistance emerged not as a spontaneous reaction but through deliberate symbolic narratives and the amplification power of social media. The findings show that such resistance was strategically nurtured, reflecting deeper tensions in a multicultural society. While the police employed humanistic communication strategies and sought collaboration with religious leaders, the outcomes were mixed, highlighting both the potential and the limits of symbolic engagement in crisis management. This study contributes to the broader discourse on public trust, symbolic politics, and cultural communication in security governance. It emphasizes the necessity of embedding legal enforcement practices within culturally sensitive and inclusive frameworks. The case of Deli Serdang reveals the complex intersections between identity, legitimacy, and authority in contemporary Indonesia.